Getting up to Speed: A Resident-Led Inpatient Curriculum for New Internal Medicine Interns - Julia B. Caton (Association of American Medical Colleges, 2019)
Introduction The transition from medical school to internship is an important milestone in medical training and often is a challenge for trainees. This resident-designed and -led inpatient curriculum for internal medicine interns was created to address common clinical scenarios and how best to manage them. Methods During the Intern Summer Curriculum, interns participated in weekly small-group sessions facilitated by senior residents. Each case-based session was structured around a clinical topic. Working in pairs with an expert faculty member as a reviewer, volunteer junior and senior residents reviewed and edited each session. During the 2 years we conducted surveys of learners and instructors in the curriculum, there were 200 intern learners and 68 resident instructors. Results The Intern Summer Curriculum was evaluated highly by all participants. Of the intern and resident survey responses, 92% (N = 77) of interns felt that the curriculum should be continued for future interns, and 100% (N = 50) of residents felt that residents should continue to teach in this program. Interns felt that the curricular content helped them better understand topics they commonly encountered and improved their ability to perform day-to-day tasks. Resident instructors felt that teaching in this program was a valuable learning experience and helped strengthen teaching skills. Discussion This resident-run inpatient curriculum for internal medicine interns can serve as a valuable learning experience for the intern learners, as well as for the resident instructors, and aid in bringing all interns up to speed at the beginning of intern year.